C-terminal acidic cluster is involved in Ca2+-induced regulation of human transient receptor potential ankyrin 1 channel - Sura, Lucie; Zíma, Vlastimil; Marsakova, Lenka; Hynkova, Anna; Barvík, Ivan; Vlachova, Viktorie (The Journal of biological chemistry, 2012)
The transient receptor potential ankyrin 1 (TRPA1) channel is a Ca(2+)-permeable cation channel whose activation results from a complex synergy between distinct activation sites, one of which is especially important for determining its sensitivity to chemical, voltage and cold stimuli. From the cytoplasmic side, TRPA1 is critically regulated by Ca(2+) ions, and this mechanism represents a self-modulating feedback loop that first augments and then inhibits the initial activation. We investigated the contribution of the cluster of acidic residues in the distal C terminus of TRPA1 in these processes using mutagenesis, whole cell electrophysiology, and molecular dynamics simulations and found that the neutralization of four conserved residues, namely Glu(1077) and Asp(1080)-Asp(1082) in human TRPA1, had strong effects on the Ca(2+)- and voltage-dependent potentiation and/or inactivation of agonist-induced responses. The surprising finding was that truncation of the C terminus by only 20 residues selectively slowed down the Ca(2+)-dependent inactivation 2.9-fold without affecting other functional parameters. Our findings identify the conserved acidic motif in the C terminus that is actively involved in TRPA1 regulation by Ca(2+).
Keywords: kationtový kanál TRPA1; Calcium; Calcium Channels; proteiny nervové tkáně; Humans; TRPA1 Cation Channel; sekvenční homologie aminokyselin; Nerve Tissue Proteins; Sequence Homology, Amino Acid; Molecular Sequence Data; molekulární sekvence - údaje; vápník; mutace; kationtové kanály TRP; lidé; zvířata; buněčné linie; simulace molekulární dynamiky; Amino Acid Sequence; Cell Line; Molecular Dynamics Simulation; Transient Receptor Potential Channels; vápníkové kanály; Animals; Mutation; sekvence aminokyselin